Pengaruh Belanja Modal, Belaja Non Modal, Penanaman Modal Asing, Dan Penanaman Modal Dalam Negeri Terhadap Kemiskinan Kalimantan Selatan - Hanifah Safitri; Muhammad Saleh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
This study was conducted to determine the effect of capital expenditure, non-capitalexpenditure, Foreign Investment (PMA), and Domestic Investment (PMDN) on the povertyrate in South Kalimantan Province.This research is quantitative. The data used in this study are secondary data fromSouth Kalimantan Province in 2008-2017. The analysis technique in this study uses multiplelinear regression analyses with time-series data.The results of this study are based on a regression analysis that capital expenditure hasa negative and significant effect on the poverty rate in South Kalimantan, non-capitalspending has a positive and not significant impact on the poverty rate in South Kalimantan,PMA has a negative and significant effect on the poverty rate in South Kalimantan, andPMDN has a negative and not substantial impact to the poverty rate of South Kalimantan.